African midwifery students' self-assessed confidence in postnatal and newborn care: A multi-country survey. (October 2021) - Sharma, Bharati; Christensson, Kyllike; Bäck, Lena; Karlström, Annika; Lindgren, Helena; Mudokwenyu –Rawdon, Christina; Maimbolwa, Margaret C.; Laisser, Rose Mjawa; Omoni, Grace; Chimwaza, Angela; Mwebaza, Enid; Kiruja, Jonah; et al.
Abstract: Background: Majority of maternal and new-born deaths occur within 28 hours and one week after birth. These can be prevented by well-educated midwives. Confidence in postnatal and newborn care skills depend on the quality of midwifery education. Objective: To assess confidence and its associated factors for basic postnatal and new-born care skills of final year midwifery students, from seven African countries. Methods: A multi-country cross-sectional study where final year midwifery students answered a questionnaire consisting of basic skills of postnatal and newborn care listed by the International Confederation of Midwives. The postnatal care area had 16 and newborn care area had 19 skill statements. The 16 skills of postnatal care were grouped into three domains through principle component analysis (PCA); Basic postnatal care; postnatal complications and educating parents and documentation . The 19 skills under the newborn care area were grouped into three domains; Basic care and care for newborn complications; Support parents for newborn care ; and Care for newborns of HIV positive mothers and documentation. Results: In total 1408 midwifery students from seven Sub-Saharan countries participated in the study namely; Kenya, Malawi, Tanzania, Uganda, Zambia, Zimbabwe, and Somaliland Overall high confidence for all domains under Post Natal Care ranged from 30%-50% and for Newborn care from 39-55%. High confidence for postnatal skills was not found to be associated with any background variables (Age, sex, type and level of educational programme). High confidence for newborn care was associated with being female students, those aged 26-35 years, students from the direct entry programmes and those enrolled in diploma programmes. Conclusions: Almost half of the study participants expressed lack of confidence for skills under postnatal and newborn care. No association was found between high confidence for domains of postnatal care and background variables. High confidence was associated with being a female, between 26-35 years of age, from direct entry or diploma programmes for newborn care area. The results of the study indicate gaps in midwifery education. Countries could use the ICM list of competencies to develop country specific standards for midwifery education. However, actual competence remains to be measured.